The Effect of Financial Performance and Women Power on Firm Value in Manufacturing Companies Listed on the Indonesia Stock Exchange Period 2019-2021 - Ikbal Lutfian Habrim Suyanto*; Dewita Puspawati (Riwayat: Educational Journal of History and Humanities, 2023)
Currently, the global economy is not doing well. For 2022, the IMF's World Economic Outlook projection is only 3.2 percent; next year, world economic growth is also expected to weaken at 2.7 percent. With inflation that tends to be high and economic growth declining, this gives a signal that the world economic situation is quite depressed. This type of research is a descriptive type of research. This research discusses the effect of Financial Performance and Women's Power on the Value of Manufacturing Companies listed on the Indonesia Stock Exchange in 2019 -2021. Determination of the sample using a purposive sampling method. The data analyzed in this study is secondary data, where the data is in the form of annual financial reports of manufacturing companies listed on the IDX for the 2019-2021 period. Based on several tests and analyses of the 193 sample companies obtained from 2019-2021 in this study, it can be concluded that concluded. This shows that financial performance and women's power significantly influence firm value. Trying to expand the sample population by taking data from several other industries to generalize the results to a wider context and considering external factors such as market conditions, competition, and economic policies in drawing conclusions and recommendations at the end of the research report.